The Cambridge Introduction to F. Scott Fitzgerald - Curnutt, Kirk (Cambridge University Press, 2013)
This study introduces F. Scott Fitzgerald to two very different audiences: those who possess only a passing familiarity with his life and work, and those who already know him thoroughly. For the former group – whether students or general readers – my overviews of his biography, his oeuvre, his historical context, and his critical reception provide the basic information necessary for appreciating his literary legacy. While assembling the essential details, I also wish to impart a working knowledge of how they have been previously presented so that newcomers may understand why their recitation has reduced some facts to commonplaces while others remain relatively ignored.